Metal–Organic Frameworks for Oxygen Storage1. (15th October 2014) - DeCoste, Jared B.; Weston, Mitchell H.; Fuller, Patrick E.; Tovar, Trenton M.; Peterson, Gregory W.; LeVan, M. Douglas; Farha, Omar K.
Abstract We present a systematic study of metal–organic frameworks (MOFs) for the storage of oxygen. The study starts with grand canonical Monte Carlo simulations on a suite of 10 000 MOFs for the adsorption of oxygen. From these data, the MOFs were down selected to the prime candidates of HKUST‐1 (Cu‐BTC) and NU‐125, both with coordinatively unsaturated Cu sites. Oxygen isotherms up to 30 bar were measured at multiple temperatures to determine the isosteric heat of adsorption for oxygen on each MOF by fitting to a Toth isotherm model. High pressure (up to 140 bar) oxygen isotherms were measured for HKUST‐1 and NU‐125 to determine the working capacity of each MOF. Compared to the zeolite NaX and Norit activated carbon, NU‐125 has an increased excess capacity for oxygen of 237 % and 98 %, respectively. These materials could ultimately prove useful for oxygen storage in medical, military, and aerospace applications.